Religious practices of Muslim women in the UK during maternity: evidence-based professional practice recommendations - Shaima M. Hassan (BMC, 2022)
Abstract Background Muslim women commonly observe certain religious practices during their maternity journey and research in this area suggests that more could be done from a service provision perspective to support Muslim women in the UK through this significant life event. Aim This study identifies Muslim women's religious practices during maternity, needs and challenges of religious practice while engaging with maternity services, and support needs from healthcare professionals. Method Qualitative mixed method study; that includes eight longitudinal interviews with first-time pregnant Muslim women, five focus groups with 23 Muslim mothers experiencing childbirth in last three years in UK, and 12 one-to-one interviews with Health care Professionals (HCPs) with previous experience working with Minority Ethnic groups. Participants recruited from local Muslim community groups and Maternity Care Provider, North West Coast, England. Data analysed using thematic analysis. Result Qualitative findings indicate common religious practices that Muslim women exercise at different stages of their maternity journey. These practices can be divided into two categories of common religious practices for Muslim women that 1) require only healthcare professionals' awareness of these practices and 2) require awareness and active involvement of healthcare professionals. Findings highlight key recommendations for healthcare professionals when addressing Muslim women's religious needs in the UK. Discussion/Conclusion This study provides evidence-based recommendations for professional practice to assist healthcare professionals in developing understanding and addressing Muslim women's religious practice needs in the UK. Further research is required to explore the impact of these recommendations for professional practice.